90=-15m-4

Simple and best practice solution for 90=-15m-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90=-15m-4 equation:


Simplifying
90 = -15m + -4

Reorder the terms:
90 = -4 + -15m

Solving
90 = -4 + -15m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '15m' to each side of the equation.
90 + 15m = -4 + -15m + 15m

Combine like terms: -15m + 15m = 0
90 + 15m = -4 + 0
90 + 15m = -4

Add '-90' to each side of the equation.
90 + -90 + 15m = -4 + -90

Combine like terms: 90 + -90 = 0
0 + 15m = -4 + -90
15m = -4 + -90

Combine like terms: -4 + -90 = -94
15m = -94

Divide each side by '15'.
m = -6.266666667

Simplifying
m = -6.266666667

See similar equations:

| 7x-(3x+11)=6-(5-3x) | | 7x=-343 | | 0.5=0.5c-2 | | 9[z+2]=45 | | 4x^4-38x+48x^2=0 | | x^2+9x+4= | | c=48+.06 | | 6(f+5)=2(f-4) | | 9y-5-6y+3=0 | | 5g=20 | | 1.5x=3X-4 | | 4(2x-3)=5x+12 | | 9x+4x+4+8=5x+3+7x | | 15x^2-19+6=0 | | p+3p+3p-2.50=13.25 | | |4|=6 | | 6=48+.06*.48 | | -1x(2x+3)=2(-4x+3) | | -12v-8(-v-8)=-2+3(v+1) | | 5+4n=25 | | 6+2w+5+1.5w+1.5w=21 | | 7(3x+1)=3x-9x | | 6[x+2]=-24 | | k/8-37=-5 | | 10=0.3x-9.1 | | 2.3q-3.5-3.1q=-1.8q-2.1 | | 5+6=14 | | 6p+9=14 | | 3x+2=64 | | 72=9s | | x/8=4.5/12 | | 4k-22=12 |

Equations solver categories